"Segmental Necrotizing Granulomatous Neuritis": A Rare Manifestation of Hansen Disease—Report of 2 Cases. (31st December 2012) - Jayalakshmy, P. S.; Prasad, P. H.; Kamala, V. V.; Aswathy, R.; Pratap, Priya
Abstract : Segmental necrotizing granulomatous neuritis (SNGN) is a rare condition affecting the nerves of Hansen disease patients. This is usually seen as a complication in association with the skin lesions of Hansen disease. Though very rare, it can also be the first presenting symptom of pure neuritic leprosy. We hereby report 2 cases of SNGN—one case of pure neuritic leprosy with initial presentation as SNGN and another, a treated case of borderline tuberculoid leprosy which relapsed with skin lesions and associated SNGN in the peripheral nerve.